Measurement of cochlear length using the 'A' value for cochlea basal diameter: A feasibility study†. (4th July 2017) - Deep, Nicholas L.; Howard, Brittany E.; Holbert, Sarah O.; Hoxworth, Joseph M.; Barrs, David M.
Abstract : Objectives : To determine whether the cochlea basal diameter (A value) measurement can be consistently and precisely obtained from high-resolution temporal bone imaging for use in cochlear length estimation. Methods : A feasibility study at a tertiary referral center was performed using the temporal bone CTs of 40 consecutive patients. The distance from the round window to the lateral wall was measured for each cochlea by two independent reviewers, a neuroradiologist and an otolaryngologist. The interrater reliability was calculated using the intraclass correlation coefficient (ICC) and the Bland–Altman plot. Results : Forty patients (19 males, 21 females) for a total of 80 cochleae were included. Interrater reliability on the same ear had a high level of agreement by both the ICC and the Bland–Altman plot. ICCs were 0.90 (95% CI: 0.82, 0.94) for the left ear and 0.96 (95% CI: 0.92, 0.98) for the right ear. Bland–Altman plot confirmed interrater reliability with all 96% of measurements falling within the 95% limits of agreement. Conclusions : Measurement between the round window and lateral cochlear wall can be consistently and reliably obtained from high-resolution temporal bone CT scans. Thus, it is feasible to utilize this method to estimate the cochlear length of patients undergoing cochlear implantation.